2019
DOI: 10.1021/acsenergylett.9b01747
|View full text |Cite
|
Sign up to set email alerts
|

Single-Particle Emission Spectroscopy Resolves d-Hole Relaxation in Copper Nanocubes

Abstract: Resolving the dynamics of photoexcited d-holes in metallic nanostructures is one step in the rational design of plasmonic photocatalysis. Here, we track the creation and relaxation of charge carriers in catalytically important plasmonic copper nanocubes using single-particle spectroscopy. We show that interband transitions dominate the absorption and emission of 60−160 nm copper nanocubes, and in contrast to gold nanorods, the LSPR is less important to the emission. We uncover the plasmonic enhancement of emis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 85 publications
1
25
0
Order By: Relevance
“…[22][23][24] Interestingly for the case of Cu nanostructures, it has recently been shown that dband holes close to the band edge exhibit relatively-long lifetimes that can even exceed those of sp-band electrons. 8,25 Thus, hot-hole devices composed of Cu nanostructures could present significant advantages for efficient photodetection in the visible regime. To date, however, only a few hot-holedriven photodetectors have been reported.…”
Section: Figure 1: Optical Generation and Collection Of Hot Holes In mentioning
confidence: 99%
“…[22][23][24] Interestingly for the case of Cu nanostructures, it has recently been shown that dband holes close to the band edge exhibit relatively-long lifetimes that can even exceed those of sp-band electrons. 8,25 Thus, hot-hole devices composed of Cu nanostructures could present significant advantages for efficient photodetection in the visible regime. To date, however, only a few hot-holedriven photodetectors have been reported.…”
Section: Figure 1: Optical Generation and Collection Of Hot Holes In mentioning
confidence: 99%
“…Our results highlighted the domination of Cu interband transition, in agreement with Cu nanocube systems. [ 30 ] As shown in Figure 1 a, the bandwidth of transmittance at visible wavelengths was narrowed by increasing the thickness of the Cu layer from 6 to 12 nm and was mainly caused by the strong free carrier absorption of the thick Cu layer. For wavelengths above 700 nm, transmission descended with the increase in Cu thickness due to the increased bound electrons available for excitation with the thick Cu film.…”
Section: Resultsmentioning
confidence: 99%
“…Our ability to manipulate and control hot carriers from metal nanostructures is currently restricted by 4 insufficient knowledge of plasmon-induced hot holes; to date, relatively few experimental studies have been reported. 28,[50][51][52][53][54][55][56][57][58] Here, we employ p-type nickel oxide (p-NiO) as a wide band gap semiconductor support to harvest hot holes from photoexcited Cu nanoparticles and enable photoelectrochemical CO 2 reduction with plasmonic Cu/p-NiO photocathodes (Figure 1a). Nickel oxide is commonly used as a hole transport material in a variety of photovoltaic and photoelectrochemical devices due to its excellent chemical stability, high optical transparency, and suitable p-type character.…”
Section: Introductionmentioning
confidence: 99%